Long-term results in patients with Lyme arthritis following treatment with ceftriaxone - Valesová, H; Mailer, J; Havlík, J; Hulínská, D; Hercogová, J (Infection, 1996)
A total of 35 patients with late stage Lyme borreliosis with involvement of the joints was followed up until 3 years after a 14 day course of 2 g ceftriaxone once daily i.v. Diagnosis was confirmed by indirect and direct microbiological methods as well as clinical signs and symptoms. Long term clinical results in 26 patients at 36 months were complete response or marked improvement in 19, relapse in six and new manifestations in four of the cases, respectively. Possible mechanisms for non-responding to therapy are discussed. Therapy was well tolerated; in no case discontinuation of treatment was necessary due to adverse drug reactions. The treatment results in this group of 35 patients with Lyme arthritis are considered successful. The data obtained are consistent with expectations based on the published experiences with ceftriaxone in this indication.
Keywords: Humans; lidé středního věku; Borrelia burgdorferi Group; Ceftriaxone; Lyme Disease; lymeská nemoc; Female; Aged; protilátky bakteriální; dospělí; Time Factors; výsledek terapie; senioři; lidé; časové faktory; Antibodies, Bacterial; Adult; Consumer Product Safety; Follow-Up Studies; ženské pohlaví; Borrelia burgdorferi komplex; Male; Middle Aged; spotřebitelská bezpečnost produktů; Treatment Outcome; Aged, 80 and over; Arthritis, Infectious; senioři nad 80 let; ceftriaxon; mužské pohlaví; infekční artritida; následné studie